2020
DOI: 10.1371/journal.pone.0241782
|View full text |Cite
|
Sign up to set email alerts
|

The bio-sonographic index. A novel modality for early detection of acute kidney injury after complex vascular surgery. A protocol for an exploratory prospective study

Abstract: Objective Acute kidney injury (AKI) is a common complication of complex aortic surgery with high mortality, morbidity and health care expense. The current definition of AKI does not allow for structural characterization of the kidneys and utilizes functional indices with substantial limitations leading to delayed diagnosis and ineffective interventions. The aim of this study is to develop a method of early detection of structural renal abnormalities that can precede and predict the occurrence of AKI in this po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…In a clinical study, SWE improved the diagnostic value of current biomarkers, suggesting its clinical application in HRS. 28 In this study, we observed an increase in renal RI and a decrease in YM in patients with liver cirrhosis and ascites when AKI occurs, indicating that the changes in the values of RI and YM were related to the decline of the patient's renal function. Subsequently, in patients who developed HRS, we found that their renal RI was significantly higher, while YM was significantly lower than that of patients with non-HRS AKI.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…In a clinical study, SWE improved the diagnostic value of current biomarkers, suggesting its clinical application in HRS. 28 In this study, we observed an increase in renal RI and a decrease in YM in patients with liver cirrhosis and ascites when AKI occurs, indicating that the changes in the values of RI and YM were related to the decline of the patient's renal function. Subsequently, in patients who developed HRS, we found that their renal RI was significantly higher, while YM was significantly lower than that of patients with non-HRS AKI.…”
Section: Discussionmentioning
confidence: 51%
“…Other studies also found that both SWE and renal stiffness tend to decrease with decreasing perfusion pressure. In a clinical study, SWE improved the diagnostic value of current biomarkers, suggesting its clinical application in HRS 28 . In this study, we observed an increase in renal RI and a decrease in YM in patients with liver cirrhosis and ascites when AKI occurs, indicating that the changes in the values of RI and YM were related to the decline of the patient's renal function.…”
Section: Discussionmentioning
confidence: 52%